Erythropoietin usage and resistance at patients with and stage renal disease [Son dönem böbrek yetersizliǧi olan hastalarda eritropoetin kullanimi ve direnci] - (:unkn) unknown (My University, 2001)
Improved practices for delivering renal healthcare services have resulted in the increased and prolonged survival of dialysis patients. Anaemia affects more than 90% of patients with ESRD. Recent studies showed that anaemia represents a significant risk factor for increased morbidity and mortality. The introduction of erythropoietin into clinical practice over a decade ago has transformed the way in which renal anaemia is managed. Resistance to erythropoietin is either failure to attain the target Hb concentration while receiving more than 300IU/kg/week of erythropoietin subcutaneously, or a continued need for such dosage to maintain the target. The most cause of resistance to erythropoietin is absolute or functional iron deficiency. In the iron-repleted patient who has an inadequate response to EPO, one should first consider whether the dose is adequate and whether the injections are actually being given and, if so whether they are being sited properly under the skin. Then the following conditions should be evaluated and treated: * Chronic blood loss * Infection/inflamation * Hyperparathyroidism/osteitis fibrosa * Aluminium toxicity * Haemoglobinopathies * Folate or vitamin B12 deficiency * Multiple myeloma * Malignancies * Haemolysis * ACE inhibitors or AT1 reseptor antagonist therapy * Inadequate dialysis.